2021
DOI: 10.26714/jkmi.16.3.2021.177-181
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berhubungan dengan Kepemilikan Jamban Sehat di Desa Penyak Lalang Kabupaten Sintang

Abstract: Latar Belakang: Salah satu permasalahan di Indonesia dalam bidang sanitasi adalah jamban sehat. Jamban sehat merupakan fasilitas sanitasi keluarga yang wajib dimiliki oleh semua rumah tangga. Data menunjukkan bahwa masih banyak masyarakat di Indonesia yang tidak memiliki jamban sehat. Desa Penyak Lalang merupakan salah satu desa di Kabupaten Sintang dimana masih banyak masyarakatnya yang tidak memiliki jamban sehat.Tujuan: Tujuan penelitian ini mengetahui faktor-faktor yang berhubungan dengan kepemilikan jamba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…This research is in line with Maulana's research in 2021, which found that there is a relationship between knowledge and ownership of healthy latrines (p.value = 0.000) [15]. This research is also consistent with Wirdawati's research in 2021 which found a relationship between knowledge and ownership of healthy latrines [25].…”
Section: The Relationship Between Knowledge and Healthy Latrine Owner...supporting
confidence: 90%
See 1 more Smart Citation
“…This research is in line with Maulana's research in 2021, which found that there is a relationship between knowledge and ownership of healthy latrines (p.value = 0.000) [15]. This research is also consistent with Wirdawati's research in 2021 which found a relationship between knowledge and ownership of healthy latrines [25].…”
Section: The Relationship Between Knowledge and Healthy Latrine Owner...supporting
confidence: 90%
“…The results of this study are in line with research conducted by only et al in 2020 which showed that there is a relationship between attitudes and ownership of healthy latrines (p=0.002). Likewise with Fitriani's research in 2021 which states that there is a relationship between attitude and ownership of healthy latrines (p=0.000) [25] In directing the right attitude, it is necessary to give an example of how to use the right toilet, so that the community will respond well. This can be started from the smallest scope, namely the family, then continued by the government and health workers through an extension program involving the community as the target object of a program from the preparation to the implementation of the program.…”
Section: The Relationship Between Attitude and Healthy Latrine Ownershipmentioning
confidence: 97%
“…Penelitian ini sejalan dengan penelitian yang dilakukan Wijayanti [18] menyatakan juga ada hubungan yang signifikan antara sikap dengan kepemilikan jamban di Dusun Tanggungrejo Desa Karangpatihan Kecamatan Balong Kabupaten Ponorogo dengan nilai P-value sebesar 0.000. Hasil penelitian ini memperlihatkan hubungan yang sangat signifikan sehingga dapat dikatakan bahwa semakin baik sikap seseorang tentang jamban keluarga maka semakin banyak keluarga yang memiliki jamban.…”
Section: Nursing Care and Health Technology Journal | Volume 2 Nomor ...unclassified
“…Seiring dengan meningkatnya status pendidikan kepala keluarga, maka kepemilikan jamban juga meningkat. Status pendidikan kepala keluarga secara positif mempengaruhi kepemilikan jamban [18].…”
Section: Hubungan Pendidikan Dengan Ketersediaan Jamban Keluargaunclassified
“…Poor sanitation will certainly have a negative impact on various aspects of life. The impacts of poor sanitation include a decrease in the quality of the environment, contamination of drinking water sources for the community, ICASI and an increase in environmental-based diseases such as diarrhea [2]. Diarrhea is a condition in which stool is excreted abnormally or not as usual.…”
Section: Introductionmentioning
confidence: 99%